Technological Features of Production of Precision Machine Parts Made of Composite Material by Extrusion Method - Huseynov, A.G. Huseynov; Abbasov, V.A.; Mammadov, Ch.M. Mammadov; Asadov, Sh.N. (Herald of Azerbaijan Engineering Academy, 2024)
In the article, in order to increase the efficiency and productivity and accuracy of the extrusion process in the production of precision machine parts made of composite material, in pressure casting machines (extruders) and thermoplastic machines, the working principle and technological losses of nozzles made of brass and copper alloys, equipped with a straight flow nozzle, are revealed. the causes of these losses have been determined.